Moringa oleifera leaf extract ameliorates collagen degradation via the inhibition of MMP‐3 expression in UVB‐induced rats - Riska Rachmania; Titiek Sumarawati; Agung Putra; Nurul Hidayah; Iffan Alif; Sofian Azalia Husain; Ade Indra Mukti; Reynaldi Suryajaya; Salma Yasmine Azzahara (Universitas Gadjah Mada, 2024)
Prolonged exposure to high‐intensity UVB induces the formation of reactive oxygen species (ROS) in skin tissue, triggering an increase in matrix metalloproteinase‐3 (MMP‐3) enzyme production and leading to collagen degradation. Moringa oleifera (MO) contains bioactive compounds known for ROS‐scavenging and anti‐inflammatory properties. However, the precise molecular mechanism of action remains unclear, requiring the inhibition of MMP‐3 activation and regulation of collagen deposition. This study aims to elucidate the potential effect of MO leaf extract‐based gel in restoring collagen deposition by reducing MMP‐3 activation in UVB irradiate‐induced collagen loss in rats. This study employed a completely randomized design, comprising four groups: a healthy group without UVB radiation, a negative control group subjected to UVB radiation and receiving a placebo, and two treatment groups exposed to UVB radiation with 5% or 10% moringa leaf extract‐based gel (MO‐5% or MO‐10%), respectively. Results showed that MO‐5% and MO‐10% significantly reduced MMP‐3 gene expression and increased collagen density compared to the negative control group (p < 0.05). Moringa oleifera leaf extract ameliorates collagen degradation by inhibiting MMP‐3 expression in UVB‐induced rats, suggesting its potential as a pharmacological and cosmetic agent for UVB‐induced skin damage.